Plan de marketing corporativo para la empresa productora y comercializadora de café “Hacienda Santa Gertrudis” del barrio el porvenir de la parroquia Malacatos de la ciudad de Loja, 2018-2021 - Espinoza Plaza, Rosa Paola (2019)
The research aims to develop a corporate marketing plan for the company "Hacienda Santa Gertrudis" producer and marketer of coffee located in the Porvenir neighborhood, Malacatos Parish, in the city of Loja. Based on a situational study of the company and market research. The methodology used to carry out the study is circumscribed within a descriptive, analytical investigation, using techniques such as, interview and survey, which, through instruments, such as a questionnaire formulated with a series of questions, obtained the information to be analyzed and comply with the achievement of objectives. To perform the external, competitive and internal analysis, the procedure that was used was the identification of the variables with their indicators, accompanied by their respective investigative source. In the external factors evaluation matrix (EFE), the PESTEC variables were investigated and the main opportunity was obtained to take advantage of information technologies (ICTs), to inform the gourmet product, and thus produce all its capacity Technological Since the quality of the product and the information offered represents an advantage in the purchase of the product. Finally, we have the competitive profile matrix (MPC), where direct and indirect competition was studied, having, as well as leading competition to the company Fapecafes, in terms of, price, media with customers, infrastructure and corporate image. Internally, research was carried out in the functional areas under study that are related to marketing: management, human talent, production and technology, market measurement and value chain analysis, whose results are reflected in the internal factor evaluation matrix (EFI), in this study the lack of publicity and creative image was identified as the main weakness and its strength, the good organizational climate, state-of-the-art machinery and product diversity. In the market research the variables were analyzed: product, price, place and promotion; In this study, it was determined that the best-selling and well-known product in the city of Loja, is the Victoria Café produced by the Fapecafes company and with respect to the company under study it was established as one of the weaknesses, not having enough information and publicity of your product. The discussion studied the factors that have the greatest relevance in the external, internal and competitive analysis. In the situational diagnosis of the company, DAFO matrix was built, for its construction the results that were embodied in the EFE and EFI matrix were copied. The Boston Consulting Group (BCG) matrix collaborated to determine the product that generates the most liquidity and the one that is about to leave the company's market, where the appropriate strategies were achieved so that the company obtains the best results during its life cycle. The strategies that were used are, product development and market penetration. The ANSOFF matrix, known as a growth vector, serves to identify growth opportunities, which resulted in two strategies, the first of market penetration, and the second product development, which are oriented towards innovation, creativity, and Quality competitiveness and implementation of product improvements in order to obtain sales. In the marketing plan proposal, each of the strategies found in the SWOT matrix is developed. Starting from the determination of objectives, choice of strategies, and finally budget. A detailed budget was obtained in the following way: in the corporate image, ATL advertising design and promotions design, a budget of 975.50 dollars, was obtained, and in the design of advertising through BTL media and the creation of a Storytelling video, a budget of 1,180 dollars. Having a total of $ 2,155.50 dollars. Suggested and approved by the company. It concludes with the execution and control of the corporate marketing plan where each objective of the proposal is fulfilled, generating compliance with the corporate image, such as business philosophy, logo design and slogan, implementation of uniforms for the company, with the intention of obtaining greater productivity with the workforce, corporate material and brand proposal in various materials needed for the company under study, fence design, posters, packaging design with emotional phrases including brand, promotion design, creation and dissemination of information in said promotional media of the Facebook page, Instagram, WhatsApp, and the management of organic waste, based on Corporate Social Responsibility and finally the creation of a Storytelling video.